Prevalence of Asymptomatic Pyuria in Patients with Type 2 Diabetes Mellitus and Its Association with Glycemia - S. L. Sagar Reddy; Sumanasa Gopala Datta; Umalakshmi Annavarapu; Satish Kumar Samal; Ranjini Chittur Yerat; Mohammed Mahrous; Tanedhar Meghanath Bhargav Theja; Ranjith Mule; Melkunte Shanthaiah Dhananjaya; Vijaya Sarathi (Annals of African Medicine, 2026)
Abstract Background: Type 2 diabetes mellitus (T2DM) is associated with an increased risk of urinary tract infections, including asymptomatic forms like asymptomatic bacteriuria or asymptomatic pyuria (ASP). However, the association between ASP (defined as elevated urinary leukocyte count without symptoms) and glycemic control remains unclear. Hence, this study was conducted to determine the prevalence of ASP in patients with T2DM and evaluate its association with glycemic parameters and urinary abnormalities. Methods: This retrospective cross-sectional study included 2843 T2DM patients attending the endocrinology outpatient department of a tertiary care center between June 2018 and May 2020. Data on urine microscopy, fasting plasma glucose, postprandial plasma glucose (PPG), and glycated hemoglobin (HbA1c) were analyzed. ASP was defined as >10 leukocytes per high-power field in urine. Results: The prevalence of ASP was 14.98%, significantly higher in females than males (30.7% vs. 6.87%, P < 0.0001). Patients with ASP were older and had significantly higher PPG and HbA1c levels compared to those without ASP. Nitrituria, proteinuria, and glucosuria were also more frequent in the ASP group. Among patients with available urine cultures ( n = 84), 61.9% showed significant bacterial growth, predominantly Gram-negative organisms, with Escherichia coli being the most common isolate (69.2%). A notable proportion of isolates exhibited multidrug resistance. Conclusions: ASP is present in approximately 15% of T2DM patients, with higher prevalence in females and association with poor glycemic control and urinary abnormalities. Given the substantial proportion of culture positivity and antimicrobial resistance, further studies are needed to clarify the clinical significance and management implications of ASP in T2DM.